2014
DOI: 10.1111/pace.12346
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Pediatric Brugada Syndrome: A Survey of Pediatric Electrophysiologists

Abstract: Responses were obtained from 83 pediatric electrophysiologists. The most common initial presentation was family history. There is a large variation in testing, particularly in the use of electrophysiology (EP) studies, drug challenge testing, and genetic testing. Despite limited treatment options, there is only consensus in the therapeutic approach to the pediatric patient with symptomatic BrS with 97% of physicians recommending an implantable cardioverter defibrillator (ICD). In the asymptomatic patient, a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 12 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…However, few data are available on the natural history in children 7,8,11 and the management of this special population has been inconsistent 12 . This study represents the largest series of pediatric BrS patients described as yet.…”
Section: Discussionmentioning
confidence: 99%
“…However, few data are available on the natural history in children 7,8,11 and the management of this special population has been inconsistent 12 . This study represents the largest series of pediatric BrS patients described as yet.…”
Section: Discussionmentioning
confidence: 99%
“…They requested tests when they perceived it would reduce 'uncertainty' [43,65], even when contrary to guidelines, for example clinicians considering breast cancer susceptibility testing in young [43] and/or unaffected relatives [55], regardless of uncertain results identified in the proband [57]. Conversely, clinicians did not consider genetic tests when they perceived such tests would not be relevant to their patients [38,39], or did not believe results would change treatment [44,52,69]. Some clinicians were concerned about potential consequences of tests perceived as 'too new' [54,63], believing a clear benefit had not yet been proven [37].…”
Section: Overview Of Tdf Factors Identifiedmentioning
confidence: 99%
“…Patient factors Patient factors relates to both tangible patient characteristics and clinicians' considerations of an individual patient. Clinicians considered patient characteristics, such as age [33], gender [41], family history [44,50,57], or particular health condition and indication for testing [33,37,67,68], when deciding if testing should be offered. Across several studies, patient interest and patients' 'escalating expectations' [36] acted as facilitators for clinicians considering offering genetic testing [36,41,42,56,63,[66][67][68], even when contrary to guidelines [15].…”
Section: Overview Of Tdf Factors Identifiedmentioning
confidence: 99%
“…In addition, special attention should be provided to those children (especially those aged 0-5 years) with syncope and/or febrile seizures who should undergo ECG to exclude the possibility of transient BrS-related AE 33 . A survey conducted among pediatric electrophysiologists found that only 3% of them recommend admission for observation of BrS children with fever 34 . Our findings suggest that a policy of lower threshold for in-hospital observation should be adopted in children, especially in Caucasians aged < 5 years.…”
Section: Discussionmentioning
confidence: 99%